2023
DOI: 10.1111/1467-8551.12710
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Relocation Ambiguity Model: A Prerequisite for Knowledge Management

Abstract: Knowledge management and manufacturing relocation have been treated as independent spheres. However, for a relocation to be fruitful, knowledge management needs to be incorporated. The purpose of this research is to shed light on the lack of knowledge management in dynamic manufacturing relocation. In particular, the research focuses on the ability to change, adapt and revert manufacturing relocation decisions, that is, the dynamic nature (or use) of the concept. A Swedish company was used as a case study. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…In addition, our study found that flexibility can directly contribute to resilience and performance, while agility can only support resilience directly and supply chain performance indirectly (via resilience). Such findings, in relation to a severe disruption context, have not yet been reported in the literature, which so far has focused on network configuration (Ivanov and Dolgui, 2020), risk management (Wulandhari et al, 2023), manufacturing relocation (Fjellström et al, 2023), the combination of internal and external competencies (Y. Li et al, 2022), supplier concentration (Jiang et al, 2023), and so on.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, our study found that flexibility can directly contribute to resilience and performance, while agility can only support resilience directly and supply chain performance indirectly (via resilience). Such findings, in relation to a severe disruption context, have not yet been reported in the literature, which so far has focused on network configuration (Ivanov and Dolgui, 2020), risk management (Wulandhari et al, 2023), manufacturing relocation (Fjellström et al, 2023), the combination of internal and external competencies (Y. Li et al, 2022), supplier concentration (Jiang et al, 2023), and so on.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…Supply chain performance refers to the ability to maintain the flow of available products and services and ensure on-time delivery in line with customer demand (Gu, Yang and Huo, 2021). Owing to the disruptions exacerbated by the COVID-19 pandemic, interest in the resilience of supply chains has gained momentum over the last few years (Fjellström et al, 2023;Gillani, Kutaula and Budhwar, 2023).…”
Section: Supply Chain Resilience and Supply Chain Performancementioning
confidence: 99%
“…(2022) apply the behavioural theory of the firm to understand how environmental performance feedback influences reshoring decisions, and Fjellström et al. (2023) propose the knowledge ambiguity framework to investigate the role of knowledge transfer in dynamic manufacturing relocation. We summarize these contributing papers in Table 1 and position them in the landscape of reshoring research as visualized in Figure 1.…”
Section: Reshoring: Past and Current Trendsmentioning
confidence: 99%
“…Reshoring decision considering stakeholders and environmental regulation (Sena et al, 2022) Reshoring of manufacturing operations in SDGs context (Choudhary et al, 2022;Fjellström et al, 2023;Zhang et al, 2022) Prior research on reshoring the localization of products and services as the future of global manufacturing cannot be ignored. Moreover, localization as a phenomenon originated from the need to offer content in various languages.…”
Section: Reshoring As a Disruptive Processmentioning
confidence: 99%
See 1 more Smart Citation